A Study into the Role of International Collaborations in Higher Education to Enhance Research Capacity for Disaster Resilience. (2018) - Amaratunga, Dilanthi; Liyanage, Champika; Haigh, Richard
Abstract: International collaborations in the context of Disaster Resilience (DR) is pivotal due to several reasons. It helps to propose ways to create more coherent international approaches on disaster risk reduction, climate change adaptation and resilience strengthening; it helps to enhance risk management capabilities by bridging the gap between science and legal/policy issues; it helps to address the issue of efficient management of trans-boundary crises. The need to optimise international cooperation in relation to resourcing research, capacity building to undertake research and facilitating its uptake is mentioned throughout the Sendai Framework for disaster risk reduction 2015-2030 (SFDRR). Given their different capacities, as well as the linkage between the level of support provided to them and the extent to which they will be able to implement the SFDRR, developing countries require an enhanced provision of means of implementation, including adequate, sustainable and timely resources, through international cooperation and global partnerships for development, and continued international support, so as to strengthen their efforts to reduce disaster risk. The purpose of this paper is to examine the level of engagement of Higher Education Institutions (HEIs) in developing countries in Asia in international collaborations to improve their Research and Innovation (R&I) capacities in DR. Based on a project entitled ASCENT (Advancing Skills Creation and Enhancement), the findings of the paper focuses on three Asian countries, i.e. Bangladesh, Sri Lanka and Thailand. Other than an extant literature review, the paper findings are drawn from a questionnaire survey carried out in eight HEIs from the said countries. There are already several regional initiatives that promote collaboration among HEIs towards building resilience. These networks should be supported and encouraged to grow. These global networks should collaborate with existing bodies to ensure that the role of higher education is understood and can be made use of. Findings of this paper supports the need for an enhanced international partnership to improve the science-policy interface in DR and to achieve the objectives of the SFDRR.